Characteristic Description of Type II Diabetes Mellitus Patients In The Working Area of Paka Indah Public Health Center - Ovelin Lay Kaperek; Muhamad Agun Gunarsa; Riska Riska (Journal of Epidemiology and Health Science, 2026)
Background: Hyperglycemia is a condition when blood glucose levels in the body are high, characterized by polyuria, polydipsia, polyphagia, severe fatigue, and blurred vision. If Diabetes Mellitus is not treated quickly, it can trigger complications such as heart disease, kidney disease, skin and nerve disorders. Objectives: To determine the characteristics of DM patients according to age, gender, education, occupation and duration of suffering. Methods: This type of research is descriptive with the location of the study at the Paka Indah Health Center, North Konawe Regency. The data collection period was carried out in January - September 2025. The sample in this study were DM patients who received health services according to standards in the period January - September 2025 as many as 25 samples from the health center's medical records. Results: The majority of patients >60 years and above are (48%), female (64%), elementary school education level (48%), working (68%), duration of suffering <5 years (68%). Conclusion: Type 2 DM patients at Paka Indah Community Health Center, North Konawe are dominated by the Early Elderly group, women, elementary school students, working, and have a duration of less than 5 years.  Keywords: Diabetes Millitus Tipe II, Heath Service, Education Status, Blood Glucose, Medical Records.